Legislative distinction of Muslims from the heretic groups based on the Qur’an and prophetic Hadith with special reference on doctrinal issues - Mohd Marzuki, Zunaidah (International Islamic University of Malaysia, 2019)
God has distinguished Muslims who follow the guidance from others in the spheres of doctrine, worship, conduct, moral, ethics, habit and so on. This article treats the issue of the legislation of distinction of Muslims from the heretic groups through analyzing the Qur’anic verses and Hadiths by applying the inductive and analytical method. The study finds eighth groups which are directly mentioned in the texts. They are the group of infidels, polytheists, the people of ignorance, the non-Muslim of non-Arabs, the people of the Book, the Zoroastrianism, the Persians and the Romans. Some of these groups even though are similar in their essence, but the focus of the legislation is on their distinct behaviors, actions and belief while the dissimilarity is reflected in their doctrine of polytheism, hyperbole in religion and in what they dispute in their doctrine of religion. In fact, these are examples that reveal the distinction of Muslims from others.